Data In The Internet of Things era: the propertization of data in light of contemporary business practices - Sidi Ahmed, Sidi Mohamed; Mohamed, Duryana (Universiti Malaysia Sarawak, 2020)
Data is at the heart of the digital age or, as some put it, “the new oil”, “the next natural resource” and the “currency of the 21st century” that everything depends on to function and operate. The Internet of Things (IoT), which aims to connect things to the Internet and interconnect them with each other, could have a huge impact on data generation and dissemination as there will be data streams from countless sources. The centrality of data and its countless value in today’s world do not, however, end contention and controversial views about its nature. Every stakeholder looks at data from his own perspective. Merchants and the business community view data as a valuable asset and commodity that could generate huge profits. In the existing legal systems, courts traditionally excluded information (data) from the ambit of property and current statutes seem to be silent about the issue of dealing with data as property. This paper attempts to study the propertization of data in light of contemporary business practices and the existing laws through consulting some relevant statutory laws and court cases. The aim of the discussion is to pay attention to the gap between business practices and current legal protection available for data or information. This paper is believed to be useful and timely as data propertization is an ongoing contentious issue that surfaces with every new wave of data-generated technology such as the IoT.